2009
DOI: 10.1007/s10750-009-9951-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential causes of enhanced transfer of mercury to St. Lawrence River Biota: implications for sediment management strategies at Cornwall, Ontario, Canada

Abstract: We examined factors and pathways involved in the transfer of mercury (Hg) to the food web in St. Lawrence River embayments near Cornwall, Ontario, where natural remediation of contaminated sediments (eventual burial by settling of cleaner sediments) has been adopted as a management strategy. Yellow perch (Perca flavescens) from one of the study zones (Zone 1) along the river by Cornwall contained significantly higher total mercury (THg) concentrations than perch from other equally contaminated zones. While THg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 25 publications
3
13
1
Order By: Relevance
“…For example, zooplankton MeHg ranged from 7.4 to 11 ng/g in the St. Lawrence River, from 6 to 161 ng/g in northern Wisconsin lakes, and from 4 to 240 ng/g in Canadian lakes [12,36,37]. In the present study, the mean concentration of MeHg in microzooplankton was approximately four times the mean amount of MeHg in microseston, which is similar to the literature values (4.6 times [12]).…”
Section: Mehg In Microzooplanktonsupporting
confidence: 87%
“…For example, zooplankton MeHg ranged from 7.4 to 11 ng/g in the St. Lawrence River, from 6 to 161 ng/g in northern Wisconsin lakes, and from 4 to 240 ng/g in Canadian lakes [12,36,37]. In the present study, the mean concentration of MeHg in microzooplankton was approximately four times the mean amount of MeHg in microseston, which is similar to the literature values (4.6 times [12]).…”
Section: Mehg In Microzooplanktonsupporting
confidence: 87%
“…Ridal et al [64] attributed significant differences in THg concentrations observed for perch but not for benthic invertebrates within contaminated zones of the Cornwall Area of Concern to prey selection, zone-specific Hg sources, and/or heterogeneity of habitat influencing Hg dynamics. For most taxa, differences between sites in biota MeHg concentrations were non-significant, with the exception of shiners (p<0.001) and juvenile smallmouth bass (p=0.0193) (both highest at CrossPower and Gorham on an among-site basis (Figure 4, and Table S4)).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the presence of dams within this system likely impose restrictions on transport of Hg to downstream reaches, affecting bioaccumulation, and the implications of dam and/or sediment removal on transport of legacy pollutants within river systems (e.g. [54, 64]) is an important avenue of continuing research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sediment samples (Zone 1, St. Lawrence River, Cornwall, ON, Canada) used in the present study were highly heterogeneous, being a composite of brown-black clayed mud with wood fibers and oil patches resulting from the historical industrial contamination of the site [23][24][25] and bacterial decay. The sediment heterogeneity therefore influenced the high variability of ambient mercury concentrations (MeHg: 2.6 AE 0.53 ng/g, n ¼ 24; total Hg: 1,212 AE 489.4 ng/g, n ¼ 35) in the samples.…”
Section: Statistical Analysesmentioning
confidence: 99%